HUBUNGAN ANTARA GAYA HIDUP DENGAN KEJADIAN HIPERTENSI PADA IBU HAMIL DI PUSKESMAS BAAMANG II SAMPIT TAHUN 2018 - hardianti aprina (Jurnal Ilmiah Kebidanan dan Kesehatan Wanita, 2018)
Background :One of the health problems in pregnancy and cause complication in 23%pregnancyishypertension.Hypertensionisoneriskfactorsfortheoccurrenceof cardiovasculardisease.Hypertensionisstronglyinfluencedbyanunhealthylifestyle.Objectives :To knowing the correlation of lifestyle with incidence of hypertension inpregnant women at baamang II public health center year 2018. Methods :The study classified in analytic, design with Cross Sectionalresearch.Researcher set the sample inside the study up to 41 sample. This study usedinstrument questionnaire who distributed to pregnant womens. The location of studyexecuted at BaamangII Public Health Center. Result :The research showing that the majority of unhealthy lifestyles total of 22respondent (53,7%) with moderate hypertension, result of correlation total of 0,897with the significant p value 0,000. Lifestyle based on food consumption patterns themajority are not well with moderate hypertension total of 20 respondent(41,0%)result of correlation total of 0,902 with the significant p value 0,000. Lifestyle basedon the adequacy of rest the majority are not well with moderate hypertension total of15 respondent (36,6%) result of correlation total of 0,887 with the significant p value0,000. Lifestyle based on physical activity the majority are not well with moderatehypertension total of 15 respondent (36,6%) result of correlation total of 0,711 withthe significant p value0,000. Conclusion :There is a significant correlation between the lifestyle with incidence ofhypertension in pregnant women at baamang II public health center year 2018.